IMPLEMENTASI KONSEP AGILE GOVERNANCE PASCA PENYEDERHANAAN BIROKRASI PADA SEKRETARIAT DAERAH PROVINSI LAMPUNG - Amantha, Goestyari Kurnia (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
Bureaucratic Simplification is a policy based on the government's desire to answer various institutional and bureaucratic problems. In principle, the bureaucratic simplification policy is carried out through 3 (three) stages, namely simplifying the organizational structure, equalizing positions, and adjusting work systems. The Lampung Provincial Government is one of the regions that has implemented bureaucratic simplification. Through various policy implementation processes, implementation performance is produced which is characterized as outcomes that have direct impacts, medium-term impacts and long-term impacts. Using a qualitative descriptive research method, the process of implementing outcome-based policies in the Regional Government of Lampung Province will be described. The research results show that through three stages of bureaucratic simplification we will see how implementation performs. The Equalization Process for 669 positions in the Lampung Provincial Government is a direct impact of the implementation of the bureaucratic simplification policy, this means that the Lampung Provincial Government has cut 669 existing structural positions. Next, through the stages of equalizing positions for 503 structural positions to functional positions, individual Civil Servants in the Regional Government of Lampung Province who previously held structural official positions were directly transformed into functional officials. Furthermore, the long-term impact is that the work system that applies to the Lampung Provincial Government from now on must be guided by Governor Regulation Number 22 of 2023 concerning Work Systems for Simplifying Bureaucracy. Where there is no more tiered bureaucracy and more uses a team work approach, making it more flexible, dynamic and agile.